Review of hydraulic performance of open-channel flow-measuring flumes - Sibale, Davis (Acta hydrotechnica, 2023)
The review explored various flumes used for open channel flow measurement and provided insight into operational concepts, discharge measurement, range of flow, head loss requirements, degree of accuracy and submergence, advantages, and limitations for use. The reviewed flumes included; Parshall flumes, Montana flumes, Cutthroat flumes, H-flumes, Trapezoidal flumes, Replogle-Bos-Clemmens (RBC) flumes, PalmerBowlus flumes and Central Baffle flumes (CBF). Based on the stage and discharge relationship, the reviewed flumes have a reasonable accuracy of ± 10 % over a wide range of flows. RBC flumes are the most accurate flumes (± 2 %). For flows that deal with a lot of sediments, most flumes have self-cleaning capability except for Palmer-Bowlus flumes and Central Baffle flumes. H-flumes have low resistance to submergence. The submergence transition for H-flumes is only 25-30 %. RBC flumes and Palmer-Bowlus flumes have the highest submergence (90 %). CBF and Palmer-Bowlus flumes need to be improved in order to have self-cleaning capability. Submerged flow corrections need to be developed and published for Palmer-Bowlus flumes and RBC flumes. The reviewed flumes effectively operate with a minimal head loss. The review has provided an insight on selection of an appropriate type of flume for flow measurement in open channels.
Keywords: accuracy; discharge; flumes; merilna korita; natančnost; open channel; potopljenost; pretok; samočiščenje; self-cleaning; submergence; tok s prosto gladino